2017
DOI: 10.1016/j.neuro.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant efficacy of antihistamine cyproheptadine in rats exposed to the chemical warfare nerve agent soman

Abstract: Organophosphate compounds, such as soman and sarin, are highly toxic chemical warfare nerve agents that cause a build-up of acetylcholine in synapses and neuromuscular junctions. Current therapies aim to prevent seizures and protect against brain injury following exposure. The present study was designed to evaluate the effectiveness of the antihistamine cyproheptadine in improving survival and controlling seizures in rats exposed to soman. Rats were pretreated with the oxime reactivator HI-6 (125mg/kg, ip) 30m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…CPH is known as a typical, first-generation antihistamine [25] with powerful anticholinergic effects [5,26]; however our previous study in cultured mouse cortical neurons demonstrated that CPH enhances I K by activating the r1R/Gi-protein/PKA pathway [9]. In the current study, using a pharmacological antagonist and agonist of r1Rs we confirmed that the effect of CPH on neuronal excitability was also mediated by r1Rs.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…CPH is known as a typical, first-generation antihistamine [25] with powerful anticholinergic effects [5,26]; however our previous study in cultured mouse cortical neurons demonstrated that CPH enhances I K by activating the r1R/Gi-protein/PKA pathway [9]. In the current study, using a pharmacological antagonist and agonist of r1Rs we confirmed that the effect of CPH on neuronal excitability was also mediated by r1Rs.…”
Section: Discussionsupporting
confidence: 80%
“…Notably, the structure of CPH is similar to that of antidepressants such as amitriptyline, imipramine, and N-methylamitriptyline [3], while the receptor-binding profile and neuron adaptation of CPH are thought to resemble those of clozapine, indicating a possible use in the treatment of schizophrenia [4]. Although CPH has neurological side-effects, such as sedation and reduced cognitive function [2], it has recently been reported to control seizures, improve survival, reduce seizure duration, and reduce the number of dying cells in the rat brain following exposure to soman [5]. These data suggest that CPH plays a role in the central nervous system, though few studies have explored its possible neurological role and the underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The antihistamine cyproheptadine has been shown to be effective in controlling seizures in experimental models (rat), including reducing the duration of seizures and the number of dying cells in the brain following soman exposure, thus improving overall survival. 72 Human butyrylcholinesterase is a stoichiometric bioscavenger which is being studied as a possible treatment for NA poisoning. It inhibits the NA in the bloodstream and prevents the NA from attacking other enzymes.…”
Section: Other Treatmentsmentioning
confidence: 99%